Analysis of experimental data of environmental cement prepared by fly ash of eggs shell and sand dune for reduction of carbon dioxid - Brahimi, Abdelghani (Data Brief, 2020)
In the recent years, the dominant cementitious materials have been industrial by products such as fly ash. This present data describes some of the cementitious products that are attracting attention in the global research community and the properties and characteristics of these materials that affect their performance such durability, mechanically properties and reduction of carbon dioxid (CO(2)). The present investigation deals with the chemical synthesis of cementitious material using fly ash of eggs shell rich in calcium(Ca) and sand dune(southern west of Algeria) rich in silica(SiO(2)).The composition of geopolymers synthesized are the most compressive resistant with a maximum stress of 49.71 MPa, the most flexible (E = 2.63 GPa) and the most ductile (εr = 65.42%).The characteristic properties of the chemically synthesized cementitious materials were analyzed by the chemical composition analysis XRF, XRD and SEM analyses.